2018
DOI: 10.1248/cpb.c17-01026
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up of Lubricant Mixing Process by Using V-Type Blender Based on Discrete Element Method

Abstract: A method for scale-up of a lubricant mixing process in a V-type blender was proposed. Magnesium stearate was used for the lubricant, and the lubricant mixing experiment was conducted using three scales of V-type blenders (1.45, 21 and 130 L) under the same fill level and Froude (Fr) number. However, the properties of lubricated mixtures and tablets could not correspond with the mixing time or the total revolution number. To find the optimum scale-up factor, discrete element method (DEM) simulations of three sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These include the evaluation of the performance of various mixer types, assessment of mixing time and operational scale, operating conditions, the optimal amount of flow aids, and the development of models [ 5 , 12 , 22 , 23 ]. Horibe et al [ 24 ] recently assessed the effect of mixing time and the concentration of flow aids on the flow properties of the end product. They found that the mixing time has a higher correlation to the flow properties than the concentration of flow aids, signifying the importance of the process and mixing conditions in improving the flow behaviour of a particulate system.…”
Section: Introductionmentioning
confidence: 99%
“…These include the evaluation of the performance of various mixer types, assessment of mixing time and operational scale, operating conditions, the optimal amount of flow aids, and the development of models [ 5 , 12 , 22 , 23 ]. Horibe et al [ 24 ] recently assessed the effect of mixing time and the concentration of flow aids on the flow properties of the end product. They found that the mixing time has a higher correlation to the flow properties than the concentration of flow aids, signifying the importance of the process and mixing conditions in improving the flow behaviour of a particulate system.…”
Section: Introductionmentioning
confidence: 99%